ENVIRONMENTAL HEALTH EMERGENCIES IN NIGERIA - AJAWVIHE PEACE CHIDIEBERE, AJAWVIHE PEACE CHIDIEBERE; IGWILO SABINA NWAKAEGO, IGWILO SABINA NWAKAEGO (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
Flooding, operational /looting, spills, structural collapse, drainage malfunction, accidents, to mention but a few, have been observed to be common in Nigeria; leading to environmental health emergencies. Environmental emergencies can occur anywhere, at anytime, but some parts of the world like Nigeria may be more prone to it; due to poor environmental management. The resultant outcome of environmental emergencies in Nigeria have summarily remained high morbidity, mortality, and economic loss. In which the causes are attributed to lack of value for the environment, as poor sanitary habits have predisposed Nigerians to suffer from high level environmental emergencies. So far, it has been difficult to prevent Environmental health Emergencies in Nigeria. Howevet; the ·currentsure ways out are: upholding environmental health through environmental sanitation, high level preparedness for emergency situations, reporting quick intervention, health education, review of environmental polices, prosecution of offenders having a sense of value for the environment, and others.